FROM TRADITIONAL TO DIGITAL: ECONOMIC EMPOWERMENT MODEL FOR SEAFOOD AND HERBAL PRODUCT COMMUNITIES IN PULAU KETAM - Dian Septiana Sari; Annisa Ilmi Faried; Tuan Zamilah Binti Tuan Husain; Widia Br. Ginting (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the transformation of traditional fishing and herbal product communities in Pulau Ketam through innovative digital empowerment strategies. Located off Port Klang, Selangor, Pulau Ketam represents a unique case study of coastal community development challenges and opportunities in Malaysia's digital economy era. The research employs a participatory action research methodology, involving 150 community members through focus group discussions, in-depth interviews, and digital literacy workshops conducted between March-September 2024. Key findings reveal that 78% of participants experienced significant income improvements averaging 45% through e-commerce platform adoption, while 65% of traditional herbal product sellers successfully transitioned to online marketing channels. The study introduces an integrated digital empowerment framework incorporating infrastructure development, capacity building, market access facilitation, and sustainable community partnerships. Results demonstrate that strategic digital intervention can preserve traditional knowledge while enhancing economic resilience, contributing RM 2.3 million to local GDP within the intervention period. This research provides valuable insights for policymakers and development practitioners working on rural digitalization initiatives across Southeast Asia.